The Relationship of Mother’s Knowledge, Attitude, and Behavior Regarding Diarrhea with the Number of Diarrhea Toddlers Taken to The Health Facility - Irin Irin; Angela Kurniadi (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2022)
Introduction: Diarrhea is the second major cause of death in toddlers in developing countries, including Indonesia. The study aims to determine the relationship between knowledge, attitudes, and behavior of mothers regarding prevention and treatment of diarrhea with the number of toddlers taken to the health facility. Methods: A cross-sectional study was involving 120 mothers who have a child with a history of diarrhea and were recruited using a simple random sampling method. Data were collected using demographic and diarrhea-related questionnaires. Fisher-Exact test was used to analyze data in univariate and bivariate with p-value ≤ 0,05 as the level of significance. Results: Most of the mother’s knowledge, attitudes, and behavior regarding diarrhea were considered fairly good, with the percentage reaching 70,8%; 66,7%; 70,8%, respectively. However, knowledge, attitude, and behavior regarding giving ORS were low. There was a significant relationship between the attitude and behavior of the respondents with the number of diarrhea toddlers taken to health facilities (p = 0,010; p = 0,000), but there was no significant relation with the respondents’ knowledge (p = 0,065). Conclusions: The attitude and behavior of mothers regarding diarrhea significantly affect the number of diarrhea toddlers taken to the health facility. Although the overall knowledge, attitude, and behavior of the mother were considered fairly good, but the knowledge, attitude, and behavior regarding giving ORS were low. Keywords: knowledge – attitudes – behavior - diarrhea – toddlers - health facilities